Epidemiology of venous thrombosis in children with cancer - Piovesan, Dana; Attard, Chantal; Monagle, Paul; Ignjatovic, Vera (Thrombosis and Haemostasis, 2014)
There has been an extensive body of research focusing on the epidemiology of thrombosis in adult cancer populations; however, there is significantly less knowledge about thrombosis in paediatric cancer populations. Thrombosis is diagnosed with increasing frequency in children being treated for cancer, and there is an urgent need to increase our understanding of the epidemiology of thrombosis in this population. Currently, there are no guidelines for identification of high-risk groups, prophylaxis or management of thrombotic complications in paediatric cancer patients. We reviewed the available literature regarding the epidemiology, mechanisms, risk factors, prophylaxis and outcomes of thrombosis in children with cancer and identified areas that require further research. The reported incidence of symptomatic venous thromboembolism (VTE) in children with cancer ranges between 2.1% and 16%, while the incidence of asymptomatic events is approximately 40%. Approximately 30% of VTE in this population is associated with central venous lines (CVL). The most common location of VTE is upper and lower extremity deep venous thrombosis (43 to 50% of events, respectively), while 50% of events in ALL patients occur in the central nervous system. Key characteristics that increase the risk of thrombosis include the type of cancer, age of the patient, the presence of a CVL, presence of pulmonary/intra thoracic disease, as well as the type of chemotherapy. Outcomes for paediatric cancer patients with VTE include post-thrombotic syndrome, pulmonary embolism, recurrent thromboembolism, destruction of upper venous system and death. Prospective studies aimed at enabling risk stratification of patients are required to facilitate development of paediatric specific recommendations related to thromboprophylaxis in this population.
Keywords: Cancer; child; epidemiology; incidence; thrombosis; paediatrics